Application of individual programs for students’ motor modes self-organization - A.S. Sheplyakov,; V.L. Kondakov,; E.N. Kopeikina,; N.V. Balysheva, (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the effectiveness of the application of individual programs for the self-organization of students' motor modes using digital technologies. Methods and structure of the study. The study was carried out at the Belgorod State Technological University named after V.G. Shukhov 980 students aged 18-20 took part in the pedagogical experiment. Throughout the experiment, for all students in the CG and the EG, motor activity was regulated in their free time at the level of the daily minimum rate of motor activity of 10,000 steps per day. For this, a bot channel was used in the Telegram application. For the EG group, the channel-bot Telegram calculated and offered options for the missing physical activity after filling out the morning questionnaire, which indicated the planned physical activity for the day. Results and conclusions. According to the data obtained, significant differences in Student's t-test between the CG and the EG were registered in all physical fitness tests. The greatest increase in indicators was observed in the EG in speed and speed-strength tests. The conclusion is made about the effectiveness of the application of individual programs for the self-organization of motor modes of students who used the Telegram-bot with programmed activity.